Does Dividend Stability Signal Firm Performance? Evidence from PT Telkom Indonesia (Persero) Tbk - Indah Lestari Anwar; Anwar Ramli (Economics and Business Journal (ECBIS), 2026)
This study analyzes the dividend policy of PT Telkom Indonesia (Persero) Tbk (TLKM) during the 2020–2025 period using a quantitative descriptive approach and a longitudinal case study based on secondary data from audited financial reports. The variables analyzed include Dividend Per Share (DPS), Earnings Per Share (EPS), Dividend Payout Ratio (DPR), Dividend Yield, and Free Cash Flow (FCF), with trend analysis using the Compound Annual Growth Rate (CAGR). The results show that DPS grows 6.05% per year, higher than EPS of 1.87%, resulting in DPR increasing from 80.00% to 93.95% in 2024. Nevertheless, strong and stable operating cash flow ensures that dividends remain supported by FCF, so there is no indication of financial distress. However, the increasing FCF-to-dividend ratio indicates the company's increasingly limited reinvestment space. The decline in net profit of 20.48% in 2025 also increases the risk of dividend policy sustainability. Furthermore, the increase in dividend yield was more influenced by stock price declines than dividend growth. This finding suggests that SOE dividend stability reflects not only fundamental performance but also institutional pressure from the government as the controlling shareholder, supporting the relevance of Agency Theory and Catering Theory in explaining dividend policy of state-owned enterprises in emerging markets